Simultaneous abdominal surgery in patients with the metabolic syndrome and obesity - K. M. Mylytsya (Zaporozhye State Medical University, 2016)
The aim of the study was to discuss the possibility and appropriateness of simultaneous operations in patients with metabolic syndrome (MS) and obesity (O). Material and methods. The analysis of 50 simultaneous operations in patients with MS and O was performed. Gender, age, medical history and clinical-laboratory features were explored. Duration of operations, the number of complications, length of hospital stay were analyzed. Results and discussion. Body mass index ranged from 33 kg/m2 to 51 kg/m2. Skin and fat flaps weight ranged from 3 to 12 kg. Weight loss of patients in one week after surgery ranged from 5 to 14 kg. There were no complications in the early and late postoperative period. Analysis of carbohydrate metabolism showed no significant differences in pre- and post-operative period. Nevertheless simultaneous abdominoplasty as corrective surgery reduces weight, improves the self-perception of body image, physical and mental components of quality of life. Conclusion. The introduction of simultaneous operations will contribute: - for state: to increase and maintain the reproductive potential of the nation, to save the hospital beds, to save finances, to reduce the incidence of metabolic forms of cancer pathology; - for the patient: performing one operation instead of two ones, allowing to go through preoperative stress, anesthesia, postoperative period and the rehabilitation period once; during one operation to solve two-three issues; during surgical treatment of main disease to prevent oncological, cardio-vascular disease, diabetes, etc. Of course, the widespread adoption of the program of simultaneous gynecology, surgery requires the dissemination of knowledge and techniques refinement. simultaneous surgery; metabolic syndrome; obesity